La conversión cristiana como cambio de actitud: aportes para una fenomenología de la conversión - Rubio, Roberto; Saldías, Roberto (Pontificia Universidad Católica del Perú, 2024)
This paper attempts to contribute to the studies of phenomenological philosophy dealing with religious conversion. Our contribution is to describe Christian conversion in phenomenological terms as attitude change; or, more precisely, as the transition from natural attitude to religious Christian attitude. The description is focused on the noetic pole of experience, especially considering the relationship between faith in the daily perceptual world, on the one side, and Christian faith in God, on the other side. Additionally, we present some challenges proper of the philosophical-phenomenological approach. On the one hand, we consider the challenges pertaining to the philosophical-phenomenological approach as such; on the other hand, we present the challenges that emerge when considering approaches that originate from other disciplines, such as Sociology or the Anthropology of Religion.

El presente trabajo intenta contribuir a los estudios de filosofía fenomenológica acerca de la conversión religiosa. Su aporte consiste en describir la conversión cristiana en términos fenomenológicos como cambio de actitud, más precisamente, como el paso de la actitud natural hacia la actitud religiosa cristiana. La descripción estará focalizada en el polo noético de la experiencia, y tendrá en cuenta, especialmente, las relaciones entre la fe en el mundo perceptual cotidiano, por un lado, y la fe cristiana en Dios, por otro. Además, se presentarán desafíos específicos de la tarea descriptiva fenomenológica. Por una parte, se considerarán aquellos inherentes al enfoque filosófico-fenomenológico; por otra, se presentarán aquellos que surgen al considerar enfoques procedentes de otras disciplinas, tales como la sociología y la antropología de la religión.
Christian Conversion as Attitude Change: Contributions to a Phenomenology of Conversion
Keywords: Conversion; Christian faith; Phenomenology of conversion; Natural attitude; Christian attitude; Conversión; Fe cristiana; Fenomenología de la conversión; Actitud natural; Actitud cristiana; https://purl.org/pe-repo/ocde/ford#6.03.01